PENDAMPINGAN IBU MENYUSUI OLEH KELOMPOK LANSIA PEDULI ASI (KLP-ASI) DALAM MENGATASI MASALAH MENYUSUI UNTUK MENCEGAH STUNTING DI KELURAHAN LUBANG BUAYA KECAMATAN CIPAYUNG - Deswani, Deswani; Mulyanti, Yuli; Ismail, Rita; Nurul M, Andini; Nur M, Azzahra; Sari A. T, Amelia; Eki R, Dea (Poltekkes Kemenkes Bengkulu, 2023)
The Exclusive Breastfeeding Program has been established by the government. However, the coverage of Exclusive Breastfeeding in 2023 in the Lubang Buaya sub-district still needs to be below the achievement of the Cipayung District, namely 51%. This community service aims to train and assist breastfeeding mothers through the Nursing Care for Breastfeeding Elderly group, formed in November 2022 in the Lubang Buaya sub-district. This activity aims to reach as many as 20 people in Lubang Buaya Village, Cipayung District, in May 2023 as many as 20 people. The method of this service activity is to assist breastfeeding mothers by KLP-ASI with as many as 15 people. Results: from the Lubang Buaya Subdistrict Office on May 20 2022. The results showed an increase in the knowledge and skills of older people in assisting mothers with breastfeeding. Conclusion: the breastfeeding mother assistance activities by the Breastfeeding Care Elderly Group / KLP-ASI were effective in helping mothers overcome the breastfeeding problems they faced that indicted by increasing the average of knowledge attainment of breastfeeding mothers, the elderly, and cadres from 84.55% to 94% (10-point increase).